2013
DOI: 10.1016/j.chemgeo.2012.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Tracing anthropogenic Hg and Pb input using stable Hg and Pb isotope ratios in sediments of the central Portuguese Margin

Abstract: a b s t r a c t a r t i c l e i n f o Hg and 201 Hg) Hg isotopes in sediment samples from core 252-16 were characterized by positive mass independent fractionation (MIF), while recent sediments from cores 252-32 and 252-35 did not reveal significant MIF, probably reflecting both the proximity to the source of anthropogenic Hg contamination (Tagus Estuary) and the importance of the CSC as a particle carrier. The multi-tracer approach, based on both stable Hg and Pb isotopic signatures, confirms anthropogenic H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 63 publications
9
53
0
Order By: Relevance
“…Previous results on Hg ores other metal deposits exhibited d 202 Hg of ∼ -0.6±0.4‰ (σ) and D 199 Hg close to 0 (Sonke et al, 2010;Liu et al, 2011;Blum et al, 2014;Hintelmann and Lu, 2003;Smith et al, 2005Smith et al, , 2008Stetson et al, 2009;Laffont et al, 2011;Yin et al, 2013a). Sediments with high THg concentrations is predominately derived from anthropogenic sources as deposition typically occurs near the source, waters are relatively turbid (thereby reducing photochemical processes) or the Hg from these sources are less susceptible to photo-reduction (Foucher and Hintelmann, 2009;Feng et al, 2010;Gehrke et al, 2011;Sonke et al, 2010;Donovan et al, 2013;Cooke et al, 2013;Ma et al, 2013;Mil-Homens et al, 2013;Gray et al, 2013Gray et al, , 2015Balogh et al, 2015;Yin et al, 2013a;Lepak et al, 2016 …”
Section: Historical Records Of Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results on Hg ores other metal deposits exhibited d 202 Hg of ∼ -0.6±0.4‰ (σ) and D 199 Hg close to 0 (Sonke et al, 2010;Liu et al, 2011;Blum et al, 2014;Hintelmann and Lu, 2003;Smith et al, 2005Smith et al, , 2008Stetson et al, 2009;Laffont et al, 2011;Yin et al, 2013a). Sediments with high THg concentrations is predominately derived from anthropogenic sources as deposition typically occurs near the source, waters are relatively turbid (thereby reducing photochemical processes) or the Hg from these sources are less susceptible to photo-reduction (Foucher and Hintelmann, 2009;Feng et al, 2010;Gehrke et al, 2011;Sonke et al, 2010;Donovan et al, 2013;Cooke et al, 2013;Ma et al, 2013;Mil-Homens et al, 2013;Gray et al, 2013Gray et al, , 2015Balogh et al, 2015;Yin et al, 2013a;Lepak et al, 2016 …”
Section: Historical Records Of Dmentioning
confidence: 99%
“…Determination of isotopic Hg signatures in sediment profiles have proven useful to better understand historical Hg loading to a variety of systems ( Jackson et al, 2004;Feng et al, 2010;Sonke et al, 2010;Cooke et al, 2013;Donovan et al, 2013;Ma et al, 2013;Mil-Homens et al, 2013;Gray et al, 2013Gray et al, , 2015Balogh et al, 2015). However, this task may be more complicated when attempting historical reconstruction for large lakes receiving loads from many tributaries with varied source signatures, contamination histories, and subject to significant changes in nutrient loading and benthos re-engineering by invasive species (Hecky et al, 2004;Rossmann, 2009).…”
mentioning
confidence: 99%
“…As a result, the initial studies of Hg isotopes suggest that their analysis within samples from sedimentary deposits, including those within riverine environments, may be used to assess both Hg sources and loading histories [105,193,232,[236][237][238]. Sonke et al [193], for example, found that within the Lot River basin, France metal refining resulted in slag residues that exhibited heavier Hg isotopic values, and both mass-dependent and mass-independent Hg isotopic signatures of contaminated sediments were significantly different (heavier) than that of the local background materials.…”
Section: Mercury Isotopesmentioning
confidence: 99%
“…It is now clear, however, that numerous inorganic and organic reactions result in Hg isotopic fractionation (Table 2), producing large variations in the Hg isotopic composition of natural and anthropogenic materials (Figure 14) [191]. These variations in Hg isotopic values may be used to assess Hg source(s), pollution histories, and transformations during biogeochemical cycling [105,[191][192][193]220]. Thus, significant effort has recently been devoted to determining the mechanisms of Hg fractionation, and how Hg isotopes may be used to assess Hg transport and fate in atmospheric, aquatic, and terrestrial systems.…”
Section: Mercury Isotopesmentioning
confidence: 99%
See 1 more Smart Citation